A ação formativa do coordenador pedagógico na transição das crianças da Educação Infantil para o Ensino Fundamental - Souza, Taís Luciana de (2018)
Law No. 11.274 / 06 brought a new organization of primary education with a duration of nine years, which led to an increase in the number of six-year-old children enrolled in the first year of primary education, implying a process of re-signification of the pedagogical practices of all who are involved in working with children who have graduated from Early Childhood Education to ensure that these students are able to develop not only as students but as subjects of childhood, which, of course, have not ceased to be. Inserting itself in this context and with the objective of ascertaining how the pedagogical coordinator can articulate the process of continuous formation of the teachers to minimize the implications of the transition of the children that leave the EMEI and join the EMEF, the present research was realized in two schools of the Municipal Education Network of São Paulo, being one of Elementary School and another, of Infantile Education, belonging to the same district and to the same Regional Directorate of Education. The methodological support was the research done through a qualitative study. The research instruments used were semi-structured interviews with the elementary school teachers and with the pedagogical coordinator of the Infantile Education of each school and documentary analysis of the attributions of the pedagogical coordinator, to sustain reflexively the proposition of formative actions. The results show that there is a great concern about the transition of students who leave early childhood education and enter elementary school, however, there is still little care for this process, which continues to be marked by disarticulation and discontinuity of pedagogical work. The research identified that not only the pedagogical coordinators of EMEIs and EMEFs need to provide formations that lead the professionals of the childhood to rethink the questions regarding the transition between the two segments, as well as the pedagogical teams acting in the Regional Directorates of Education. These teams can promote planned spaces that culminate in formative actions between pedagogical coordinators and teachers of Early Childhood Education and Elementary Education, so that the curricular proposals included in the document "Integrative Curriculum of the Paulistan Childhood" become effective and allow the subjects involved to feel part of the transition process in the school curriculum of six-year-olds